Effect of cracks on the stability of dump slope - Bharati A.K.; Ray A.; Rai R.; Shrivastava B.K. (My University, 2025)
Maintaining the stability of overburden dumps in opencast mines is a major challenge. Instability in dump slope occurs because of many inherent factors, cracks formed by mining activities, and natural climatic conditions etc. have been considered in this study. Numerical simulation of the dump slope has been performed using RS2 (Rocscience) software based on the finite element method (FEM). In simulation, the effect of cracks by considering the crack inclination, crack location from the crest of the dump slope, and effect of crack length and crack inclination at critical failure surface location has been analyzed. It has been found for the given conditions that cracks at a distance less than 7.5m from the crest of the slope for inclination 30° to 50° have the least stability and crack at critical failure surface location for inclination 40°, and 50° have a significant effect on the stability of the dump slope for all the considered crack length. © 2020, Books and Journals Private Ltd.. All rights reserved.